Multi-Scales Behaviour of Materials : Special Topic Volume with Invited Peer Reviewed Papers Only - Karama, Moussa (Applied mechanics and materials, 2012)
This volume focuses on the development of methods, for predicting the behaviour of materials, so as to be able to design materials having specific properties. This requires a multi-scale material modeling framework that is based upon the fundamental laws of physics and links the electronic modeling hierarchy all the way from the atomistic and mesoscale modeling regimes up to macroscopic material behaviour. It is evident that such a framework cannot be based upon rigid formal parameterizations alone, but must emerge from a detailed understanding of the mechanistic behaviour of materials, a prof.